Menstrual disorder and associated factors among medical students in Uganda: a cross sectional study - Jimmy Odongo Ogwal; Edward Ojuka; Richard Migisha; Rosemary Namayanja; Samuel Okello; Ronald Ouma Omolo; Victor Muyambi; Jolly Joe Enyang; Abel Obeny; Ronald Ogwang; Caleb Angulo; Jesse Steward Opwoya; et al. (Discover Medicine, 2025)
Background: Menstrual disorders (MD) affect 75% of women worldwide and account for the majority of morbidity in women of childbearing age. Heavy and prolonged menstruation are linked to severe anemia and its sequelae, irregular menstruation predisposes females to unwanted pregnancies, which can result in unsafe abortion with associated maternal injuries and even death. Furthermore, students suffering from PMS, dysmenorrhea, or heavy menstruation are more likely to miss lectures and exams. Objectives: We determined the prevalence and factors associated with menstrual disorders among undergraduate medical students at Mbarara University of Science and Technology (MUST) in southwestern Uganda. Methods: We conducted a cross-sectional study in the Faculty of Medicine (FOM) at MUST from 2nd October, 2023 to 1st November, 2023 using consecutive sampling among the female undergraduate students, we included students from 19 to 45 years and excluded those who were either pregnant or breastfeeding. Sociodemographic, gynecological, lifestyle and clinical data were obtained through self-administered questionnaires. The prevalence of menstrual disorders was the proportion of participants with any of dysmenorrhea, Premenstrual Syndrome (PMS), infrequent, frequent, prolonged, heavy or irregular Menstruation. Modified Poisson regression analysis was used to evaluate associations between menstrual disorders and independent variables. Results: A total of 290 students were enrolled with mean age 23.93 (±4.40) years. The prevalence of menstrual disorders was 85.6% (249/290) (95%CI 81.83–89.90), indicates that these issues may be a common concern for young women, especially those in academic environments. Having stress [aPR 1.13, 95% CI (1.03–1.24), p=0.007], being below 24 years [aPR 1.12, 95% CI (1.01–1.25), p=0.034] and being underweight [aPR 1.15, 95% CI (1.08–1.22), p<0.001] were independently associated with Menstrual disorders. Conclusion: More than three-quarters of medical students at MUST experience menstrual disorders, highlighting a significant health concern in this population. These findings emphasize the need for integrating menstrual health education and stress management programs into medical curricula. Health policies should prioritize screening and management of menstrual disorders, with recommendations for wellness programs such as yoga, sports, and creative activities to support student well-being.
Keywords: Menstrual disorders; Medical students; Stress; Prevalence; Uganda